Quantification of benefits of digitalisation of process data of a craft distillery - Kankenga, Daniel Pembe (University of the Witwatersrand, Johannesburg, 2024)
Craft breweries and distilleries are frequently not digitalised, making them susceptible to regular production losses. Despite this, benefits of investing in digitalising process are often not easily measurable. The purpose of this research study is to develop a comprehensive framework to quantify the benefits of digitalising process data within the brewing process of a craft distillery. The study was based on historical data from Primal Spirit Distillery, located in Johannesburg, South Africa. The data underwent validation through the application of data visualisation techniques as well as a comprehensive statistical analysis. Mass balance calculations were conducted for the mash tun and fermentation processes, as well as an overall mass balance assessment to compare potential alcohol content with actual alcohol produced. Statistical tools, such as correlation analysis and the student t-test, were used to interpret the data and identify opportunities for digitalisation to enhance productivity. The study concluded with an economic analysis, assessing the financial implications and profitability of digitalising process data in the distillery. The conclusion of the research study highlighted the significant potential for improving productivity in craft distilleries and breweries through the digitalisation of process data. The developed framework proved effective in quantifying these benefits, encompassing steps such as historical data collection, visualisation, mass balance, statistical analysis, intervention planning, and economic feasibility assessment. The analysis revealed considerable sugar loss during mashing, with an average of 16.45%. Fermentation resulted in alcohol levels within the acceptable range in only 53.66% of instances, with an average alcohol deviation of 32.29%. The distillery, on average, operated at 67.71% of its potential alcohol production capacity. Correlation analysis and t-tests identified key variables requiring careful monitoring to reduce deviations and enhance productivity. While there are more economical alternatives, the optimal solution involves the use of affordable storage platform for process data, process control instrumentation devices, such as sensors and flow meters. The economic study indicates that a R 200,000 investment to digitalise the distillery's process data could boost productivity by 30%. The investment would be fully recovered in 4 months, with a 25.43% profit gain within 5 months. However, actual profitability may range between 10 to 20% due to potential unforeseen circumstances during production.
A research report submitted in fulfillment of the requirements for the Master of Science (MSc) in Chemical Engineering, In the Faculty of Engineering and the Built Environment , School of Chemical and Metallurical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digitalisation; historical process data; craft distilleries; framework; data analysis; data accuracy; mass balance; statistical analysis; productivity; brewing process; alcohol deviation; sugar loss; economic analysis; return on investment; profitability; SDG-9: Industry, innovation and infrastructure